Human Enhancement and Transhuman Technologies in Slovak Media Discourses - Magda Petrjánošová (Communication Today, 2025)
In this article we report on and discuss our initial insights from a media analysis, whose goal was to map media discourses around human enhancement and transhuman technologies in the Slovak media. The main timeframe for material collection was 2009-2013. We conducted a search of the Slovak Press Agency (SITA) media outputs database, using thematically chosen keywords. Based on a critical discursive analysis of the material collected, we suggest that three basic discourses (with several subvariations) can be found in the Slovak press: A) Transhuman technologies and the survival of humans as a species; B) Transhuman technologies and superhumans; C) Transhuman technologies and changes in basic human nature (with consequences for ethics, morals and religions). We decided to concentrate on the closely related, intertwined discourses A and B. We included all the kinds of media targeting the general public because we were interested in the whole spectrum of potentially different ‘renderings’ of the topic aimed at all possible audiences. However, the differences found were smaller than expected. Our findings do not indicate that certain kinds of media (according to ‘seriousness’ or preferred themes) favour a specific presentation of transhuman topics, nor that they favour some discourses and completely ignore others. But we did find an appalling lack of any critical discussion from different morally anchored perspectives that would provide specific answers to dilemmas around prohibiting / regulating some technologies, at the national or international level, which are already partly relevant now and may become extremely relevant in the near future.